Aligning goals: supervisor-supervisee’s expectations in undergraduate final year project - Mohd Noor, Maizura; Turiman, Syamimi; C. Suppiah, Puspalata; Aziz Hussin, Anealka; Aidin Druckman, Zachariah (Universiti Teknologi MARA, Kedah, 2025)
Communication is one of the essential mediums of interaction towards fulfilling various final-year undergraduate research projects (FYPs) offer valuable opportunities for students to apply conceptual and theoretical knowledge to enhance their scientific reasoning skills. However, as novice researchers, they rely substantially on their supervisors’ guidance. Expectations may differ throughout the collaboration process, which can cause frustration and impede progress. Despite the complexity of the undergraduate supervisory relationship, existing research has primarily focused on postgraduate level and qualitative analyses. This study aims to address this gap by investigating the expectations held by both supervisors and undergraduates involved in FYPs. Key areas examined include methodological decisions, references and materials, policies and procedures, study plans and completion of tasks, checking of drafts, and language accuracy and academic tone. Matching sets of questionnaires were administered to undergraduates and supervisors to determine and compare their expectations of each other. Overall, the results reveal that both parties' expectations varied across the areas investigated. This research contributes to a deeper understanding of the dynamics in undergraduate supervisory relationships, shedding light on areas where improvements may be needed to enhance the overall quality of FYPs and supervision.